DCDS: Data centric dispatcher selection protocol for cellular enabled VANET communication. (5th March 2019) - Dhanasegaran, Kalaivani; Soundrapandiyan, Rajkumar
Summary: The Vehicular Ad‐hoc Network (VANET) is one of the emerging research areas in recent days, in which accomplishing the robustness and security are the demanding tasks. To obtain these objectives, various offloading‐based techniques are developed in the traditional works. Still, it remains with the limitations of high mobility, no assurance for data acceptance, and limited applicability for multiple data exchange units. Thus, this paper aims to develop a Data Centric Dispatcher Selection (DCDS) algorithm based on data offloading for a secure information exchange in VANET. It aims to enable the cellular‐based VANET connection by using the application layer protocol without taking the Pending Interest (PI)‐based information. Also, the Content Centric Network (CCN) concept is utilized to exchange the data between for upcoming internet. In this environment, the position of own vehicle and neighboring vehicle are known to each vehicle by using the Global Positioning System (GPS) and security messages. Moreover, the communication does not depend on the device's name, but it depends on the content name in CCN. Because of the availability of multiple interfaces in CCN, there is no content loss in the network. During simulation, various performance measures are used to evaluate the performance of the proposed technique, which includes throughput, packet loss rate, average end‐to‐end delay, total Satisfied Interest Packet (SIP), Forwarded Interest Packet (FIP), and average Interest Satisfactory Delay (ISD). Also, the superiority of this paper is proved by comparing it with some existing techniques such as Internet Protocol Television Quality of Service (IPTV‐QoS), Michael Oche (MO), and RobUst Forwarder Selection (RUFs). Abstract : This paper aims to develop a Data Centric Dispatcher Selection (DCDS) algorithm based on data offloading for a secure information exchange in VANET. It aims to enable the cellular‐based VANET connection by using the application layer protocol without taking the Pending Interest (PI)‐based information. Also, the Content Centric Network (CCN) concept is utilized to exchange the data between for upcoming internet.